Swadeshi within the Framework of Ethnocentrism in the Health and Wellness Sector: Preserving Cultural Traditions in a Globalized Society (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The concepts of satyagraha and swadeshi play an essential role in Gandhi's approach to life.Gandhi believed that the whole of man's actions constituted a single, inseparable totality. The main aimof the study is Swadeshi Within the Framework of Ethnocentrism in The Health and Wellness Sector. Theresearcher has employed the non-probability sampling techniques of purposeful and conveniencesampling for this study. Indians today still hold on to their cultural traditions, despite living in aglobalized and modern society.